1979
DOI: 10.3758/bf03329439
|View full text |Cite
|
Sign up to set email alerts
|

Type A behavior and normal habitual sleep duration

Abstract: The responses of 361 college students to the Jenkins Activity Survey and a self-report sleep questionnaire were used to demonstrate an inverse relationship between normal habitual sleep duration and level of Type A behavior. The possibility that patterns of sleep may be implicated in the development of Type A behavior in some individuals was considered. 185This paper reports a correlation between response to the Jenkins Activity Survey (JAS) and self-reported normal habitual sleep duration that may provide fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

1979
1979
2006
2006

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Our data (3,4,5 ) suggest that as the Type A pattern develops, sleep may be shortened to capture more tlme for wakeful activity. In these studies.…”
mentioning
confidence: 86%
“…Our data (3,4,5 ) suggest that as the Type A pattern develops, sleep may be shortened to capture more tlme for wakeful activity. In these studies.…”
mentioning
confidence: 86%
“…Next, from appropriate pools of eligible individuals, three sleep groups were randomly selected: a group of 20 male and 20 female variable sleepers (defined as persons who reported at least a 2-h range in their regular duration of sleep), a group of 20 male and 20 female short sleepers (defined as persons who slept, without reported variation, 6 h or less each night), and a group of 20 male and 20 female long sleepers (defined as persons who slept, without reported variation, 9 h or more each night). It should be noted that the two extreme sleep groups were included as a means of duplicating the extremes of the continuum used by Hicks et al (1979). Thus, these groups provided the reference points that were necessary to tie the results of this research to that study .…”
Section: Methodsmentioning
confidence: 99%
“…As predicted, it was found that the variable sleepers showed significantly less Type A behavior than either of the other two groups. These data further elaborate the possible role of sleep behavior in the management of stress.Recently, the San Jose group (Hicks, Pellegrini, Martin, Garbesi, Elliott , & Hawkins, 1979) reported finding a significant inverse relationship between normal habitual sleep duration and level of Type A behavior as defined by score on the Jenkins Activity Survey (JAS) . In discussing the implications of this relationship, we speculated that the relatively higher stress susceptibility of Type A individuals might, in part, be a consequence of the relatively shorter sleep durations that tend to be characteristic of these individuals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that Type A college students tend to sleep less ( 4 ) and are mice as likely to report sleep problems ( 3 ) than Type B students. In a comprehensive discussion of sleep.…”
mentioning
confidence: 99%